FITOAKUMULASI MERKURI OLEH AKAR TANAMAN BAYAM DURI (AMARANTUS SPINOSUS LINN) PADA TANAH TERCEMAR - Sopyan, Sopyan; Sikanna, Rismawaty; Sumarni, Ni Ketut (Univ. Tadulako, 2014)
The studies entitled Fitoakumulasi Mercury By Root Crops Spinach Thorns ( Amarantus spinosus Linn ) In Contaminated Soil has been done with the purpose of remediation time know effect on the ability of plant roots to absorb mercury thorn spinach and determine the maximum concentration of mercury that accumulates in the roots of spinach plants thorns in the remediation time . The method used in this study is defined as phytoremediation technology recovery , cleanup , removal or reduction of contaminants in soil or water by using the help of plants . Time remediation consists of 4 stages 7 , 14 , 21 and 42 days . While planting media concentration is 25 ppm , 50 ppm , 75 ppm and 100 ppm . The maximum concentration of adsorbed on the roots of spinach plants thorns is 0 , the dry weight of roots harvested at a institusen empire with a concentration of 100 ppm , the remediation time is day 14 ( P2 ) . And the ability of the roots to absorb mercury remediation significantly different with respect to time .